Trends in prescribing anti‐obesity pharmacotherapy for paediatric weight management: Data from the POWER Work Group. Issue 1 (2nd September 2020) - Borzutzky, Claudia; King, Eileen; Fox, Claudia K; Stratbucker, William; Tucker, Jared; Yee, Jennifer K; Kumar, Seema; Cuda, Suzanne; Sweeney, Brooke; Kirk, Shelley; on behalf of the POWER Work Group,
Summary: Introduction: To better inform the field of obesity medicine, we set out to describe the current use of pharmacotherapy meant to improve patient weight status among a group of clinicians connected through the Paediatric Obesity Weight Evaluation Registry (POWER), as well as reasons behind clinicians' use or non‐use of the medications. Methods: Paediatric weight management (PWM) programs participating in POWER were asked to complete a program profile survey in 2014 (n = 30) and 2017 (n = 33); questions about pharmacotherapy use were included. Descriptive statistics were used to identify: (a) the proportion of PWM programs offering obesity pharmacotherapy; (b) the medications most commonly prescribed; and (c) reasons among non‐prescribers for not offering pharmacotherapy. Results: The 2014 and 2017 surveys were completed by 29 PWM programs (97%) and 30 PWM programs (91%), respectively. Twenty‐one programs completed both surveys. In 2014, 10 (34%) programs reported offering pharmacologic agents specifically for weight control, whereas in 2017, 16 (53%) reported offering pharmacotherapy for a primary indication of weight loss. Metformin was reported as the most commonly used agent in 2014, and topiramate in 2017. Largest reported increases in use over time were for topiramate and phentermine. Discussion: Our survey results demonstrate that a majority of this group of PWM programs offered pharmacotherapy to promote weight loss in patients with complications or associated medical conditions. There was a trend indicating increasing use over time, despite the significant gap regarding pharmacotherapy use in the literature. Conclusions: These data suggest the need for (a) additional robust paediatric drug trials to further develop the evidence base guiding use or non‐use of pharmacotherapy in paediatric weight management, and (b) increased understanding of both facilitators and barriers to prescribing anti‐obesity pharmacotherapy for youth with obesity.